Investigation into Some of Engineering Properties of Soil: A Case in Study in Seka Town, Jimma Zone, Ethiopia (American Journal of Geospatial Technology, 2022)
The main aim of this study is to investigate some of the engineering properties of soils found in Seka town in order to know the nature of the soil and also to give information for the design, construction and environmental assessment, so that suitable foundation can be recommended for better design and construction in the town. Laboratory tests were carried out including specific gravity ranges 2.65 to 2.77, natural moisture content, Atterberg limits, UCS  ranges 143.52kN/m2 to 352.92kN/m2, compression index 0.23 and 0.39, and swelling index 0.19 and 0.02, MDD ranges from 1.180 g/cm3 to 1.480 g/cm3, and OMC range 35.9% to 48.00% and permeability ranges 3.75*10-5 to 2.75*10-4 cm/sec. Based on the results of this study, the grain size distribution indicates all soil samples have more than 90% fine grained material. Clayey silty type of soil is dominantly located in the study area.